Civil Remedies for Environmental Damage: Exploring the Effectiveness of Carbon Trading as a Tool for Restoration in Indonesia - Rahmawati, Diah Ayu; Haryono, Haryono; Endarto, Budi; Soraya, Joice; Munawaroh, Siti (Eastasouth Institute, 2025)
This paper discusses the effectiveness of carbon trading as a civil remedy for environmental damage in Indonesia through a juridical normative analysis. The research explores Indonesia's legal framework governing carbon trading, its implementation, and its alignment with principles such as